Revisiting the Role of Private Schooling on Children Learning Outcomes: Evidence from Rural India. Issue 2 (September 2019) - Singhal, Karan; Das, Upasak
In the view of increasing preference of private schooling in India, this article assesses its impact on learning outcomes for rural children from 8 to 11 years. Despite earlier attempts to study the issue, this article stands out in two ways. Firstly, it addresses the problems arising because of non-random selection of children attending private schools. Secondly, it also presents an all-India estimate unlike most studies which have dealt largely with few states. Our results show the performance of children attending private school to be significantly better than those from public schools. This difference is evident among 'low-fee' private schools as well. However the private schooling premium differ across regions and groups, and there are several other concerns regarding affordability, access and segregation which require further deliberation and debate. JEL: I2, I21, I28